Improved Sleep Associated With Triamcinolone Acetonide Extended-Release Injections for Knee Osteoarthritis: Use of a New Real-World Registry - Michael A. Mont, MD; Jennifer H. Lin, PhD; Andrew I. Spitzer, MD; Vinod Dasa, MD; Adam Rivadeneyra, MD; David Rogenmoser, DO; Andrew L. Concoff, MD; Mitchell K. Ng, MD; Mary DiGiorgi, PhD, MPH; Stan DySart, MD; Joshua Urban, MD; William M. Mihalko, MD, PhD (Arthroplasty Today)
Background: Since the mid-20th century, knee osteoarthritis (OA) has doubled in prevalence, costing more than $27 billion annually. This study aimed to compare 6 nonoperative treatment options for knee OA (cryoneurolysis with superficial nerve block, cryoneurolysis with deep nerve block, intra-articular hyaluronic acid injections, nonsteroidal inflammatory drug injections, IA corticosteroids, and IA triamcinolone extended release [IA-TA-ER]) over 4 months, analyzing their effects on sleep disturbance, a component of health-related quality of life. Methods: All patients with knee OA and received nonoperative interventions with at least 4 months of follow-up between 2021 and 2024 were identified from the Innovations in Genicular Outcomes Research registry, a multicenter novel real-world registry. Patient demographics were gathered/analyzed, adjusting for age, sex, study site, Kellgren-Lawrence grade, baseline score of pain severity/function, pain-catastrophizing, and analgesic use in each assessment. Sleep disturbance was assessed via least-square-means relative to the average population, with multivariate linear regressions used to assess changes pretherapy/post-therapy. Results: Patients administered IA-TA-ER had decreased sleep disturbance relative to other cohorts (least-square-means 52.3; 95% confidence interval: 50.5-54.0; P < .03). Patients receiving IA-TA-ER or IA corticosteroids achieved achieving minimum clinically important difference for sleep disturbance improvement, 63% and 57%, respectively. Pairwise comparison revealed patients receiving IA-TA-ER were 2 times more likely to achieve minimally clinically important difference for improved sleep relative to other cohorts (P < .05). Conclusions: Extended-release triamcinolone injections are associated with decreased sleep disturbance relative to other treatments, in both degree of improvement and proportion of patients. Further studies should examine the potential beneficial effects of IA-TA-ER on other aspects of health-related quality of life.